Tik Tok dalam Tinjauan Administrasi Publik Di Indonesia - Dandan Haryono (CV. ALIM'SPUBLISHING, 2025)
The development of digital technology has transformed the landscape of public administration in Indonesia. One notable digital platform is Tik Tok, a short-video sharing application that has gained significant popularity among the public. This journal aims to analyze the role and implications of Tik Tok in the context of public administration in Indonesia. The research method employed is a literature study and secondary data analysis. The findings indicate that Tik Tok has been utilized by government and public institutions to enhance public engagement, disseminate public information, and promote government programs. However, challenges related to privacy issues, ethics, and user data security remain. This journal concludes that the utilization of Tik Tok in public administration must be carefully managed and aligned with the principles of good governance.